Design and develop a microcontroller-based motor frequency driver - Fadhlan Tajudin (Universiti Malaysia Perlis, 2009)
This thesis was showed a project of Design and Develop Microcontroller-based Motor Frequency Driver. This driver actually was an inverter circuit which can vary the frequency in order to control the single phase induction motor. The project was divided into two main portions. First was on software designing and second was on hardware construction. The basic principal of this microcontroller was change in the value of input voltage frequency as done in this project which 40 Hz, 30 Hz, 20 Hz, and 10Hz. Microcontroller was chooses in order to produce the variable frequency for controlling the single phase induction motor. The microcontroller was used to produce the pulse generation, so by varying the pulse generation may produce the variable frequency. The second part was on hardware construction. This part actually worked as an inverter. This inverter generally use PWM control signal for producing AC output voltage. The circuit of this inverter was used H-bridge topology. This topology was choosing because it low cost and less harmonic production. As the sinusoidal output of this system varied in frequency, it controlled the single phase induction motor speed.